Endobronchial Foreign Body Removed by Flexible Bronchoscopy Using the Trendelenburg Position - Huang, Pei-Ming; Kao, Ming-Wei (The Thoracic and Cardiovascular Surgeon, 2012)
Foreign body (FB) aspiration causes various symptoms and sometimes leads to severe conditions. Therefore, its prompt diagnosis and removal are essential to avoid complications. Flexible bronchoscopy is both a safe and effective method to confirm suspected cases of FB aspiration and to facilitate FB removal. However, few articles have dealt with the proper techniques for removal of FB in younger versus older patients based on anatomical variation. We report FB aspiration in an old male patient in whom attempted removal with flexible bronchoscopy failed but was later achieved by repeated flexible bronchoscopy with the patient in the trendelenburg position.
Keywords: airway foreign body; bronchoscopy